Sensitivity analysis for parameter identification in quasi-static poroelasticity - Lecampion, Brice; Constantinescu, Andrei (International journal for numerical and analytical methods in geomechanics, 2005)
This paper is devoted to the formulation of the direct differentiation method and adjoint state method in quasi‐static linear poroelasticity. We derive the strong and weak formulation of both methods and discuss their solutions using the finite element method. The techniques are illustrated and tested on two numerical examples for the case of isotropic and homogeneous material. The presented formulations can be extended to more complex behaviour in poromechanics. Copyright © 2004 John Wiley & Sons, Ltd.